Electrical power unit of the transformer oil centrifugal cleaning unit - Hnatov, A. V.; Arhun, Shch.; Bagach, R. V.; Nechaus, A. O.; Tarasova, V. V.; Ruchka, O. O.; Don, A. V.; Patlins, A.; Гнатов, А. В.; Аргун, Щ. В.; Багач, Р. В.; Нечаус, А. О.; et al. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. Cleaning transformer oil is one of the important engineering tasks, whose solution is associated with significant material and energy expenditure. Due to the increase in electricity consumption at modern automobile companies (firms, organizations, service stations, etc.), the load on transformer substations increases and the requirements for reliability of electrical and electronic devices become more complicated. This, in turn, leads to the problem of cleaning and recycling of transformer oil. Goal. The goal is the research and development of an efficient unit for centrifugal cleaning of transformer oil with a drive control system that provides automation of the start and braking mode of the drive. Methodology. Analytical methods of research, methods of the theory of electric machines and electric drives are used, as well as the methods of calculating electric circuits. Also, methods of analysis of circuits and control of power electronics devices, principles of operation and methods of control of static converters are used. Results. The structural scheme of the unit for cleaning transformer oil is developed. The calculations of the main elements of the power block of the transformer oil cleaning unit are performed. The block diagram of the voltage converter with frequency f = 50 Hz to alternating voltage with frequency f = 400 Hz is developed. Control circuits of the electric drive of the centrifugal separator are chosen. The analysis of operation of electric drive control circuits is carried out and the principles of their work concerning two components are considered: the regulated rectifier and the inverter. Originality. The scheme of the converter of alternating three-phase current with voltage of 220 V and frequency of 50 Hz, into alternating three-phase current with voltage of 220 V and frequency of 400 Hz is developed. This frequency, in addition to providing the necessary characteristics of the oil separator, allows you to develop a converter device of a relatively small weight and volume, and also provides its high reliability. Practical value. Utilizing the used transformer oil in this way will solve several problems at once. It is possible to reduce the initial production of transformer oil. The issue of waste oil disposal is being resolved leading to the solution of the environmental aspect of this problem. All this will reduce the cost of oil poured into transformers and the operating cost of transformer substations.
Електрична силова частина приладу відцентрового очищення трансформаторної оливи
Keywords: power supply system; power transformer; transformer oil; oil separator; electric power; transformer substation; система електропостачання; силовий трансформатор; трансформаторна олива; нафтовий сепаратор; електроенергія; трансформаторна підстанція; 629.341; 10.30977/AT.2219-8342.2021.48.0.101